Modeling of Wind Energy on Isolated Area - Hachemi Glaoui; Harrouz Abdelkader; Ismail Messaoudi; Hamid Saab (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, a model of the wind turbine (WT) with permanent magnet generator (PMSG) and its associated controllers is presented, The increase of wind power penetration in power systems has meant that conventional power plants are gradually being replaced by wind farms. In fact, today wind farms are required to actively participate in power system operation in the same way as conventional power plants. In fact, power system operators have revised the grid connection requirements for wind turbines and wind farms, and now demand that these installations be able to carry out more or less the same control tasks as conventional power plants. For dynamic power system simulations, the PMSG wind turbine model includes an aerodynamic rotor model, a lumped mass representation of the drive train system and generator model. In this paper we propose a model with an implementation in MATLAB / Simulink, each of the system components off-grid small wind turbines.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.4859